Transcending the slow bimolecular recombination in lead-halide perovskites for electroluminescence - Guichuan Xing (Nature Portfolio, 2017)
Slow bimolecular recombination in three-dimensional halide perovskites represents a fundamental limitation for electroluminescence efficiency. Using time-resolved spectroscopy Xinget al. demonstrate that this limitation can be overcome by employing van-der-Waals-coupled multiple quantum well structures.